The Role of Service Innovation, Customer Satisfaction, Brand Loyalty, and Word-of-Mouth Marketing on Business Growth of MSMEs - Jadmiko, Eko Priyo; Wahyuni, Ira; Mu'is, Ahmad; Kowey, Wylda Olivia (IJBLE Scientific Publications Community Inc., 2025)
This study explores the impact of service innovation, customer satisfaction, brand loyalty, and word-of-mouth (WOM) marketing on the business growth of Micro, Small, and Medium Enterprises (MSMEs). Using data collected from 300 MSME owners and managers, the research employs descriptive statistics, correlation analysis, and multiple regression to examine the relationships between the key variables. The findings reveal that customer satisfaction is the most significant predictor of business growth, followed by brand loyalty, WOM marketing, and service innovation. The study also highlights the interconnectedness of these factors, suggesting that a holistic approach integrating service innovation, customer satisfaction, brand loyalty, and WOM marketing is crucial for MSMEs to sustain growth and remain competitive. Practical recommendations are provided for MSME owners and managers to enhance business performance through customer-centric strategies, innovation, and brand-building efforts.